2022
DOI: 10.1111/nph.17926
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear genome of a pedinophyte pinpoints genomic innovation and streamlining in the green algae

Abstract: Summary The genomic diversity underpinning high ecological and species diversity in the green algae (Chlorophyta) remains little known. Here, we aimed to track genome evolution in the Chlorophyta, focusing on loss and gain of homologous genes, and lineage‐specific innovations of the core Chlorophyta. We generated a high‐quality nuclear genome for pedinophyte YPF701, a sister lineage to others in the core Chlorophyta and incorporated this genome in a comparative analysis with 25 other genomes from diverse Vir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Within the chlorophytes, prasinophytes (e.g., Chlorodendrophyceae, Nephroselmidophyceae, Mamiellophyceae) have usually been considered to comprise a clade, but their relationships are disputed. Phylogenomic analyses suggest that prasinophytes are paraphyletic and comprise successive sister lineages to the core chlorophytes (Figure 2) [11,22,27]. The ancestor of Chlorophyta likely diversified in marine environments, leading to the evolution of the core chlorophytes that subsequently radiated into marine, freshwater, and terrestrial environments [11,28].…”
Section: Interrelationships Of Archaeplastidamentioning
confidence: 99%
“…Within the chlorophytes, prasinophytes (e.g., Chlorodendrophyceae, Nephroselmidophyceae, Mamiellophyceae) have usually been considered to comprise a clade, but their relationships are disputed. Phylogenomic analyses suggest that prasinophytes are paraphyletic and comprise successive sister lineages to the core chlorophytes (Figure 2) [11,22,27]. The ancestor of Chlorophyta likely diversified in marine environments, leading to the evolution of the core chlorophytes that subsequently radiated into marine, freshwater, and terrestrial environments [11,28].…”
Section: Interrelationships Of Archaeplastidamentioning
confidence: 99%
“…As an evolutionary plant biologist, I have enjoyed recent works on land plant evolution (de Vries & Archibald, 2018), the anatomy and evolution of lycopsid rooting structures (Hetherington & Dolan, 2016), the evolutionary success of ferns (McElwain, 2011) and discussion on the need for more nonseed plant model organisms (Rensing, 2017). Some of my favourite research papers include: studies by Xu et al (2022) and Repetti et al (2022) of the genome of Pedinomonas minor, identifying the genomic evolution of chlorophytes; analysis by Clark et al (2016) of the evolution of fern genome traits; the work by Barba-Montoya et al (2018) to constrain the timing of the diversification of angiosperms; and that of Brockington et al (2015) which found that lineage-specific radiations of key biosynthetic genes explain betalain pigmentation in the flowering plant order Caryophyllales. All of these inspiring works have helped to stimulate ideas and discussion, as well as providing excellent reviews of the literature.…”
Section: What Are Your Favourite New Phytologist Papers Of Recent Yea...mentioning
confidence: 99%
“…(2022) and Repetti et al . (2022) of the genome of Pedinomonas minor , identifying the genomic evolution of chlorophytes; analysis by Clark et al . (2016) of the evolution of fern genome traits; the work by Barba‐Montoya et al .…”
Section: What Are Your Favourite New Phytologist Papers Of Recent Yea...mentioning
confidence: 99%
“…One of the most frequent applications of Dollo parsimony has been in reconstructing the gains and losses of genes in the lineages leading to major multicellular eukaryotic groups, including land plants (Bowles et al, 2020), animals (Fairclough et al, 2013; Najle et al, 2023; Paps & Holland, 2018), and brown algae (Cock et al 2010). It has been applied to examine patterns of gene gain and loss in the evolution of novel trophic modes or in the adaptation to specific environments in fungi and their relatives (Mikhailov et al 2017, Galindo et al, 2018, Galindo et al 2021, Mikhailov et al 2022), in green algae (Repetti et al 2022), and in red algae (Cho et al 2023). Dollo parsimony has also been employed to investigate the evolution of gene gains and losses that may have led to physiological changes such as those underlying the evolution of Wolffia australiana , the smallest known flowering plant (Park et al, 2021).…”
Section: Introductionmentioning
confidence: 99%